Analisis Pendapatan Petani Organik di Kecamatan Delanggu, Kabupaten Klaten - Eva Trisanti (Jurnal Dinamika Sosial Ekonomi, 2002)
The research entitled Farmer Income Analysis of Organic Rice at Delanggu subdistrict, Klaten district generally was directed to study the use of input and cost of production and farmer income of organic rice cultivation that is try to be developed, particularly at Segaran village. The background of this researchwas intensive agriculture activities that caused highly dependence on agriculture chemical. The activities lead to the negatively environment impact and chemical residue in consumed food. Organic farming produced safe food for people's health at in also mean as holistic approach towards sustainable agriculture as well as to protected the environment. The results of this search showed that in comparison to nonorganic farming, organic rice productivity was lower than that of nonorganic one (respectively 4000,05 kg/ha and 4181,30 kg/ha grain yeld), cost of production of organic rice cultivation was lower than that of nonorganic one respectively Rp 2.375.895 arul R 2.684.300 per ha, organic rice farmer income was higher than that nonorganic one Rp 3.435.780 and Rp. 2.751.390 per ha).Keywords : organic farming, rice productivity, cost-income analysis